The Relationship Between Conformity and Brand Switching Intention on Adolescent Handphone Brand - Syarifah Fajriyah; Komarudin Komarudin (Prosiding University Research Colloquium, 2021)
This study aims to determine the relationship between conformity with brand switchingintentions of cellphone brands among adolescents in Sungailiat Bangka district. Thehypothesis in this study is that there is a positive relationship between conformity withbrand switching intentions of cellphone brands in adolescents. Subjects in this study were190 adolescents in Sungailiat Bangka sub-district, aged 16-21 years. The data collectionprocess in this study used two scales; they are conformity scale and brand switchingintention scale. The conformity scale consisted of 46 items while the brand switchingintention consisting of 45 items. The data analysis technique used the product-momentcorrelation technique to find out more about the relationship between the independentvariables, namely conformity and dependent variables, namely the intention of brandswitching. The researcher found that the calculation result of r ^ 2 was 0.999 with apercentage of 99.9% and a p-value of 0.000.